Tekanan Kapitalis dan Dinamika Wanatani Krui di Sumatera - David E Gilbert; Virtuous Setyaka (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
This study discusses processes that changed Krui's damar agroforests. We use the idea of a 'capitalist squeeze', where factors of reproduction - drought, patterns of inheritance, and relations of local trade - combine with government and agribusiness pressures to explain these changes. We integrate historical data about damar agroforestry with information about recent deforestation and oil palm plantations throughout Krui. The results of participant observations, in-depth interviews with 12 informants, and focus group discussions with 3 groups show that previous collaborative efforts failed in protecting the Krui damar forest from extensive logging, mostly by the arrival of sawmills paying high prices for damar wood and smallholders’ preference for quick cash incomes from palm oil. Attention to the capitalist squeeze brings a focus to the need to create social relations that are just, inclusive, and egalitarian in the production of the resin itself